GRAND DESIGN PERENCANAAN PEMBANGUNAN EKONOMI BERBASIS EKONOMI KERAKYATAN DALAM UPAYA MENCAPAI PEMBANGUNAN BERKELANJUTAN DI KABUPATEN MALANG - Prasetyia, Ferry; Wulandari, Farah (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
The objective of this research is to analyse the possibility of community economybased (ekonomi kerakyatan) implementation in Malang district in order to achievesustainable economic development. This reseach state that there are four stages incommunity economy based design: first, mapping the leading economic sectors inMalang District. Second, mapping of socio-political conditions surrounding thecommunity. Third, identify the existing institutional order. Fourth, designing anappropriate form of partnership in order to accommodate the common good of thegovernment, private sector, and society.Keywords: community economy based, partnership, Malang district.